A text messaging-based intervention to increase physical activity among persons living in permanent supportive housing: Feasibility and acceptability findings from a pilot study. (February 2019) - Rhoades, Harmony; Wenzel, Suzanne; Winetrobe, Hailey; Ramirez, Magaly; Wu, Shinyi; Carranza, Adam; Dent, David; Caraballo Jones, Monika
Objective: Persons who have experienced homelessness and are living in permanent supportive housing experience high rates of health and mental health problems. Given that physical activity is associated with improved health outcomes and persons with homelessness histories report high rates of cell phone use, phone-based interventions to increase physical activity may be effective for improving health and wellbeing among persons in permanent supportive housing. Methods: To understand the acceptability and feasibility of a cell phone-based physical activity intervention in this population, this 6-week pilot study enrolled 13 persons living in permanent supportive housing. Participants were eligible if they had completed their final, 12-month follow-up interview in a larger, longitudinal study of persons moving into permanent supportive housing in the Los Angeles area, spoke English, and reported comorbid chronic physical and mental health conditions. For the study duration, participants wore a pedometer, received multiple weekly motivational text messages on set days (at times selected by the participant), and responded via text to weekly depression screeners and requests to report their weekly step totals, as recorded by their pedometers. Follow-up interviews asked open-ended questions about study participation and satisfaction. Results: Participants were 53 years old on average, most were female (54%), and most were African-American (62%). Changes to people's physical activity levels were limited, but participants reported increased quality of life during the intervention period. Interviews revealed that the intervention was well received and enjoyable for participants. Conclusions: The efficacy of utilizing cell phones to improve health and wellbeing among adults living in permanent supportive housing requires further research, but these pilot findings suggest that such interventions are feasible and acceptable.